An analysis on paradoxical gender equality+ policies and the violence in Brazil - Souza, Renan de (Faculdade de Ciências e Letras - Unesp - Araraquara., 2020)
Brazil records alarming rates of epidemic violence against women and LGBTQ+. According to statistics, the country ranks as the fifth most violent for women and the deadliest in the world for homosexuals. On the other hand, progressive policies to support both groups have been implemented by different public administrations in the last decades generating remarkable milestones. Despite being considered as cutting-edge, those actions have not necessarily translated into a reduction of violence. One explanation for these paradoxes between progressive policies to protect women, LGBTQ+ and the frequent violence against these groups, might be found in historical, cultural, and religious roots. This article highlights that, notwithstanding that some progress was made in Brazil, the rise of conservative and far-right groups may undermine all the advancement reached in the last decades, which could lead to the aggravation of the gender-based violence in the country.